Australomesitius gen. nov. (Hymenoptera, Bethylidae: Mesitiinae), an unexpected new genus from Australia - Barbosa, Diego N.; Azevedo, Celso O. (Zootaxa, 2016)
Mesitiinae include 218 species classified in 21 genera. Hitherto all species are confined to Old World (Afrotropical, Oriental and Palaearctic Regions). However most of their species are reported from Mediterranean areas, and few species are recorded from Northern areas of Palaearctic Asia. While visiting Queensland Museum Daniele Mugrabi sort part of it wet collection and got a bizarre specimen, which represents an undescribed genus of Mesitiinae. Besides, this specimen has the body surface densely punctate, characteristic never recorded to Mesitiinae species, and a combination of characters which does not fit any of the known genera Mesitiinae. The primary aim of this work is to describe this new genus, as well as to compare it with the other genera of the Mesitiinae.